"Looking for One's Life": Trapped Mobilities and Adventure in Morocco. Issue 1 (1st June 2019) - Bachelet, Sébastien
Abstract : This article examines how "irregular" migrants from West and Central Africa make sense of their trapped mobility in Morocco: for many, crossing into Europe has become almost impossible, returning to home countries "empty-handed" a shameful option, and staying very difficult in the face of repeated infringement of their rights. I explore the limits of contemporary depictions of a "migration crisis" that portray migrants south of the Mediterranean Sea as simply en route to Europe and fail to engage with (post)colonial entanglements. The article recalibrates the examinationof migrants' lived experiences of stasis and mobility by exploring the emic notion of "adventure" among migrants "looking for their lives." A focus on how migrants articulate their own (im)mobility further exposes and defies the pitfalls of abstract concepts such as "transit migration, " which is misleading in its implication of a fixed destination.